The effects of oral glutamine on cisplatin-induced genotoxicity in Wistar rat bone marrow cells - Mora, L. D.; Antunes, LMG; Francescato, H. D.; Bianchi, MLP (Elsevier B.V., 2002)
Several studies have suggested that dietary supplementation with antioxidants can influence the response to chemotherapy as well as the development of adverse side effects that result from treatment with antineoplastic agents. The emphasis of the present study was to investigate whether the administration of a single dose of oral glutamine had any protective effect against cisplatin-induced clastogenicity. Cisplatin was administered to Wistar rats either alone or after treatment with glutamine. The rats were treated with glutamine (300 mg/kg b.w.) by gavage 24 h before the administration of cisplatin (5 mg/kg b.w., i.p.) and then sacrificed 24h after treatment with cisplatin. Glutamine significantly reduced (by about 48%) the clastogenicity of cisplatin in rat bone marrow cells. The antioxidant action of glutamine presumably modulates the clastogenic action of cisplatin. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: glutamine; chromosome aberrations; rat; cisplatin